Strategic threat health response in Australia capital cities: Predicting the optimum locations for field hospitals through geospatial analysis - Mazen Baazeem; Estie Kruger; Marc Tennant (Wiley, 2024)
Abstract Objective The advent of the COVID‐19 pandemic has accentuated the critical importance of epidemic preparedness within national healthcare systems. This study presents a geospatial analysis aimed at optimising the placement of field hospitals in Australia to ensure adequate healthcare access during pandemics. Methods The latest census data from the Australian Bureau of Statistics were integrated with the spatial locations of current emergency departments within Australian capitals. Buffer zones with a 7.5 km radius were created around the public emergency departments (EDs). Buffer zones outside the 7.5 km radius that exhibited high population densities were categorised into high‐density (red), moderate‐density (yellow) and low‐density (green) zones to prioritise and tailor healthcare responses during a pandemic. The identification of high‐density population areas outside the ED radius enabled the stratification of potential sites for ED facilities. Results Ninety‐one potential field hospital sites were identified across Australia's capital cities. The findings indicate that the addition of these sites would place over 95% of the population within a 7.5 km radius of an ED facility. This network of proposed sites is designed to serve a spectrum of population densities, ensuring equitable healthcare access for both densely populated urban centres and less populated areas. Conclusions This study underscores the potential of field hospitals to strengthen Australia's public health system against emergencies. By advocating for the creation of 91 field hospitals within a 7.5 km reach for over 95% of urban dwellers across major cities, it demonstrates a strategic approach to ensure comprehensive ED coverage. Drawing on international examples, including China's Fangcang hospitals, the USA's post‐acute care (PAC) facilities and the United Kingdom's National Health Service (NHS) Nightingale Hospitals, it highlights the need for healthcare agility and scalability, especially during pandemic outbreaks. The research presents a blueprint for field hospital deployment, marking a significant advancement in public health logistics and protection across Australia's varied demographic and geographical landscapes.